Superlattice-based plasmonic catalysis: concentrating light at the nanoscale to drive efficient nitrogen-to-ammonia fixation at ambient conditions - Boong, Siew Kheng (2023)
Plasmonic catalysis promises green ammonia synthesis but is limited by the need for co-catalysts and poor performances due to weak electromagnetic field enhancement. Here, we use two-dimensional plasmonic superlattices with dense electromagnetic hotspots to boost ambient nitrogen-to-ammonia photoconversion without needing co-catalyst. By organizing Ag octahedra into a square superlattice to concentrate light, the ammonia formation is enhanced by ≈15-fold and 4-fold over hexagonal superlattice and disorganized array, respectively. Our unique catalyst achieves superior ammonia formation rate and apparent quantum yield up to ≈15-fold and ≈103 -fold, respectively, better than traditional designs. Mechanistic investigations reveal the abundance of intense plasmonic hotspots is crucial to promote hot electron generation and transfer for nitrogen reduction. Our work offers valuable insights to design electromagnetically hot plasmonic catalysts for diverse chemical and energy applications.